Contributing Factor Influencing Flood Disaster Using MICMAC (Ciliwung Watershed Case Study) - Dwi Ariyani; Mohammad Yanuar Jarwadi Purwanto; Euis Sunarti; Perdinan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Flood disaster is the most common disaster in Indonesia, flood events continue to increase and occur almost every year during the rainy season, on average caused by extreme rainfall above 100 mm, with the number of losses increasing every years, there are many factors that affect One of the causes of flooding is human activities resulting in changes in land use in the form of settlements and agricultural land. This paper aims to present a conceptual reference from the implementation results using software assistance, to determine the level of influence and dependent variables. The method used to assess the most influential factors on flood events, especially in the Ciliwung watershed, is by using Cross-Impact Matric Multiplication Applied to Classification (MICMAC). From the 11 contributing factors analyzed based on the Matrix of Direct Influence (MDI) and Matrix of Indirect Influence (MII) it is known that rainfall and distance from the river are the variables that have the most influence. While the variables with the greatest dependence based on MDI and MII are land cover, slope, population density and river waste, with institutions experiencing a larger variable displacement compared to other variables. The results of the identification of these contributing factors can be used by stakeholders to be careful of each factor as input in anticipating influencing factors.